Clinical Profile and Treatment Outcomes of Acute Retinal Necrosis in a Tertiary Eye Care Centre in Nepal - Shrestha, Priyanka; Manandhar, Anu (Nepalese Journal of Ophthalmology, 2024)
Introduction: Acute retinal necrosis (ARN) is a rapidly progressive, necrotizing herpetic infection, commonly leading to retinal detachment with significant visual morbidity. Most common causative agent belong to the herpesvirus family. It commonly occurs in healthy immunocompetent individuals. Early diagnosis of disease is important in order to start the treatment timely. Systemic antivirals and intravitreal antiviral therapy along with steroids are the main stay of treatment. Our study is a retrospective study of 5 years. We studied the patient demographics, presenting features, treatment outcome and complications of acute retinal necrosis in a tertiary care center in Nepal.Objective: Methodology: A total of 14 eyes of 13 patients were included in the study. This study is a hospital based retrospective study done in the Uveitis and Vitreoretinal department of a tertiary eye care center. Records of all patients diagnosed with Acute Retinal Necrosis between May 2013 to May 2018 were included in this study. Hospital data of these subjects including patient demographics, presenting symptoms, clinical signs, treatment received and treatment outcome were noted and analysed.Result: The mean age of the patients was 45.1 years ± 14.9 years. Sixty-nine were males and 92.3% had bilateral involvement. The mean duration of onset of symptoms was 22.4 days ± 19.5. The most common presenting symptom was decreased vision (78.6%). Among the 13 patients 10 received intravenous acyclovir, 1 received intravenous ganciclovir and 2 patients received oral acyclovir for initial systemic therapy.Conclusion: The most common complication was cataract followed by retinal detachment.